2018
DOI: 10.4314/tjpr.v16i11.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saffron oral capsule on anxiety and quality of sleep of diabetic patients in a tertiary healthcare facility in southeastern Iran: A quasi-experimental study

Abstract: Purpose: To determine the effect of oral capsule of saffron (a herbal medicine) on anxiety and quality of sleep of diabetic patients of a tertiary healthcare facility in Zabol, Iran in 2016. Methods: This was a quasi-experimental study on 50 diabetics of Zabol who met the inclusion criteria. Participants were randomly split into two groups (control and test). Anxiety and quality of sleep were evaluated by Spielberger Anxiety Inventory and Pittsburgh Sleep Quality Index (PSQI). Participants in the intervention

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 8 publications
0
26
1
Order By: Relevance
“…We included 8 studies with 431 participants [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Table 1 ). One study was reported in two reports (Lopresti et al, 2020; Lopresti et al, 2021) and was referred to as Lopresti et al, (2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We included 8 studies with 431 participants [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Table 1 ). One study was reported in two reports (Lopresti et al, 2020; Lopresti et al, 2021) and was referred to as Lopresti et al, (2021).…”
Section: Resultsmentioning
confidence: 99%
“…Five of the eight studies were conducted in high-income countries [ 24 , 25 , 26 , 27 , 31 ], and three studies were conducted in middle-income countries [ 28 , 29 , 30 ]. Four studies recruited participants from healthcare settings [ 24 , 28 , 29 , 30 ], and three recruited participants from social media, posters, and local newspapers [ 25 , 27 , 31 ]. One study did not mention the setting from which the participants were recruited [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted by Kell et al [15], saffron at dosages of 22 mg/day and 28 mg/day for 4 weeks significantly improved the quality of sleep in healthy adults. In another study, after saffron intake at a dosage of 300 mg/day for 7 days there were beneficial effects in reducing anxiety and improving the quality of sleep among diabetic patients [35]. Also, in an animal study by Masaki et al [36], crocin increased the total time of non-REM sleep in mice.…”
Section: Discussionmentioning
confidence: 99%